The Edinburgh companion to First World War periodicals - Demoor, Marysa; Dijck, Cedric van; Van Puymbroeck, Birgit (Edinburgh University Press, 2023)
The first reference book on First World War newspapers and magazines from the home front to the front lines.
Keywords: World War, 1914-1918 -- Periodicals.; World War, 1914-1918 -- Press coverage.; Guerre mondiale, 1914-1918 -- Périodiques.; Guerre mondiale, 1914-1918 -- Couverture de presse.; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh.; Press coverage; Literary reference works.; Encyclopaedias & reference works.; General & world history.; European history.; Warfare and Defence.; 1914-1918; Periodicals